Pendampingan Pengembangan Merek Produk UMKM di Belitung Timur - Wahyudi, Triyono Arief; Iskandar, Donant Alananto (LPMP Imperium, 2021)
This Community Service (PKM) program was implemented as a form of mentoring for Micro, Small, and Medium Enterprises (MSMEs) in East Belitung to develop product brands amid the impact of the COVID-19 pandemic. The goal of this activity was to improve MSMEs' understanding and ability to build strong, attractive product brands that align with market characteristics. The implementation method included observing partner needs, training in brand development strategies, and conducting business screening practices involving 40 MSMEs. The results of the activity indicated that partners gained insight into the importance of branding, formulated brand development strategies for existing and new products, and determined e-commerce strategies that align with product and consumer characteristics. This mentoring activity is expected to increase the competitiveness and sustainability of MSMEs in East Belitung.